Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the equation [tex]\(4x^2 + 4ax + \left(a^2 + b^2\right) = 0\)[/tex].
1. Identify the coefficients:
- The equation is of the form [tex]\(Ax^2 + Bx + C = 0\)[/tex]
- In this case:
[tex]\[A = 4, \quad B = 4a, \quad C = a^2 + b^2\][/tex]
2. Use the quadratic formula:
The quadratic formula states that the solutions of [tex]\(Ax^2 + Bx + C = 0\)[/tex] are given by:
[tex]\[ x = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
3. Substitute the coefficients into the quadratic formula:
[tex]\[ x = \frac{-4a \pm \sqrt{(4a)^2 - 4 \cdot 4 \cdot (a^2 + b^2)}}{2 \cdot 4} \][/tex]
4. Simplify inside the square root:
[tex]\[ x = \frac{-4a \pm \sqrt{16a^2 - 16(a^2 + b^2)}}{8} \][/tex]
[tex]\[ x = \frac{-4a \pm \sqrt{16a^2 - 16a^2 - 16b^2}}{8} \][/tex]
[tex]\[ x = \frac{-4a \pm \sqrt{-16b^2}}{8} \][/tex]
5. Simplify the square root:
[tex]\[ x = \frac{-4a \pm 4i b}{8} \][/tex]
6. Simplify the fractions:
[tex]\[ x = \frac{-4a}{8} \pm \frac{4ib}{8} \][/tex]
[tex]\[ x = \frac{-a}{2} \pm \frac{ib}{2} \][/tex]
7. Express the solutions:
[tex]\[ x = -\frac{a}{2} - \frac{ib}{2} \quad \text{and} \quad x = -\frac{a}{2} + \frac{ib}{2} \][/tex]
Therefore, the solutions to the quadratic equation [tex]\(4x^2 + 4ax + (a^2 + b^2) = 0\)[/tex] are:
[tex]\[ x = -\frac{a}{2} - \frac{ib}{2} \quad \text{and} \quad x = -\frac{a}{2} + \frac{ib}{2} \][/tex]
1. Identify the coefficients:
- The equation is of the form [tex]\(Ax^2 + Bx + C = 0\)[/tex]
- In this case:
[tex]\[A = 4, \quad B = 4a, \quad C = a^2 + b^2\][/tex]
2. Use the quadratic formula:
The quadratic formula states that the solutions of [tex]\(Ax^2 + Bx + C = 0\)[/tex] are given by:
[tex]\[ x = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \][/tex]
3. Substitute the coefficients into the quadratic formula:
[tex]\[ x = \frac{-4a \pm \sqrt{(4a)^2 - 4 \cdot 4 \cdot (a^2 + b^2)}}{2 \cdot 4} \][/tex]
4. Simplify inside the square root:
[tex]\[ x = \frac{-4a \pm \sqrt{16a^2 - 16(a^2 + b^2)}}{8} \][/tex]
[tex]\[ x = \frac{-4a \pm \sqrt{16a^2 - 16a^2 - 16b^2}}{8} \][/tex]
[tex]\[ x = \frac{-4a \pm \sqrt{-16b^2}}{8} \][/tex]
5. Simplify the square root:
[tex]\[ x = \frac{-4a \pm 4i b}{8} \][/tex]
6. Simplify the fractions:
[tex]\[ x = \frac{-4a}{8} \pm \frac{4ib}{8} \][/tex]
[tex]\[ x = \frac{-a}{2} \pm \frac{ib}{2} \][/tex]
7. Express the solutions:
[tex]\[ x = -\frac{a}{2} - \frac{ib}{2} \quad \text{and} \quad x = -\frac{a}{2} + \frac{ib}{2} \][/tex]
Therefore, the solutions to the quadratic equation [tex]\(4x^2 + 4ax + (a^2 + b^2) = 0\)[/tex] are:
[tex]\[ x = -\frac{a}{2} - \frac{ib}{2} \quad \text{and} \quad x = -\frac{a}{2} + \frac{ib}{2} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.